Impacts of stocking densities on bioeconomics and profitability of mud spiny lobster (Panulirus polyphagus Herbst, 1793) cultivation in sea cages - Arkronrat, Wasana; Konsantad, Rungtiwa; Leearam, Chonlada; Deemark, Prapapron; Srisupawadee, Chatchai; Oniam, Vutthichai (Agriculture and Natural Resources, 2024)
Importance of the work: Optimal stocking densities are crucial for maximizing the yield of aquatic species. However, the impact of stocking densities on bioeconomics and profitability is also important but has received less attention. Therefore, this study was conducted to identify the optimum stocking density for lobster farming, with a focus on bioeconomics and profitability.Objectives: To examine the effects of varying stocking densities on the bioeconomic performance and profitability of rearing mud spiny lobster (Panulirus polyphagus) in sea cages.Materials and Methods: The experiment involved rearing lobsters in sea cages (2.5 m × 2.5 m × 2.5 m, for width, length and height, respectively) at three different lobster densities per cage: 15 (low), 30 (medium) or 45 (high) or about 1, 2, and 3 individuals (ind)/m3, respectively. The lobsters were fed once daily with trash fish at about 10% of the lobster biomass, for 90 d (n = 3).Results: Survivability varied significantly after 30 d, with the high-density group having the lowest survival rates throughout the rearing period. Absolute growth, average daily growth, and the specific growth rate differed significantly among the groups by the end of the rearing period. As the stocking density increased, growth performance declined and the feed conversion ratio worsened. While the survival rate in the medium-density group was lower than in the low-density group, the medium-density group had a higher total yield than the low-density group and a net return 21.22% greater than for the high-density group. In contrast, the low-density group was not cost-effective. Furthermore, the sensitivity analysis indicated that the medium-density group was the most efficient for mud spiny lobster cultivation, providing the highest economic returns compared to both the low-density and high-density groups across negative and positive test scenarios, including testing increased environmental costs. Main finding: The stocking density at 2 ind/m3 was optimal for mud spiny lobster farming because it balanced growth performance, survival and economic profitability. The higher density (3 ind/m3) reduced the growth and survival rates, while the lower density (1 ind/m3) was unprofitable.